(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE To determine the diagnostic accuracy of the Mentzer index for diagnosis of iron deficiency anaemia by taking ferritin level as the gold standard. MATERIAL & METHODS This investigation was conducted within the Pediatric Department of Lyari General Hospital, Karachi, employing a cross-sectional study design alongside a non-probability consecutive sampling methodology. The subjects of this study comprised pediatric patients aged between 6 months and 12 years who were diagnosed with anemia (Hb ≤ 11 g/dL, Hct ≤ 32%); individuals with a history of blood transfusion, infectious diseases, malignancies, or renal dysfunction were not included in the study. The diagnostic criteria were established utilizing the Mentzer index (≥13) and serum ferritin levels (< 12 ng/mL). Statistical evaluation was executed using SPSS version 26, while adhering to a 95% confidence interval.RESULTS The study participants were pediatric patients from 6 months to 12 years (mean age 8.90 ± 2.71 years, 55.1% female; 44.9% male). The mean concentration of hemoglobin was found to be 8.97 g/dL with 64.1% of the patients ranging in the level of hemoglobin from 7-9 g/dL. A Mentzer Index exceeding 13 was identified as a reliable indicator, accurately detecting 90.2% of instances of iron deficiency anemia (IDA), while a Mentzer Index of 13 or lower correlated with 89.3% of subjects exhibiting normal ferritin levels. The Mentzer Index revealed a sensitivity of 90.24%, a specificity of 89.33%, and an overall diagnostic accuracy of 89.90%, thus corroborating its utility in the detection of IDA when serum ferritin is utilized as the definitive reference standard. CONCLUSION Our research substantiates the efficacy of the Mentzer Index as a reliable, cost effective, and non-invasive instrument for the screening of Iron Deficiency Anemia (IDA), particularly in environments where serum ferritin assessments are not readily accessible. With elevated sensitivity, specificity, and predictive values, this methodology serves as an essential resource for the early identification and distinction of IDA from alternative types of anemia. Nonetheless, subsequent multicenter investigations with expanded sample populations and heterogeneous demographics are imperative to refine the established cutoff values and to further corroborate its diagnostic precision across various contexts.